2019
DOI: 10.1177/1545968319832605
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Benefits of Combined Aerobic and Cognitive Training on Fluid Intelligence and the Role of IGF-1 in Chronic Stroke

Abstract: Background. Paired exercise and cognitive training have the potential to enhance cognition by "priming" the brain and upregulating neurotrophins. Methods. Two-site randomized controlled trial. Fifty-two patients >6 months poststroke with concerns about cognitive impairment trained 50 to 70 minutes, 3× week for 10 weeks with 12-week follow-up. Participants were randomized to 1 of 2 physical interventions: Aerobic (>60% VO 2peak using <10% body weight-supported treadmill) or Activity (range of movement and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
102
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(104 citation statements)
references
References 71 publications
0
102
0
2
Order By: Relevance
“…Future research should explore the benefits of combining aerobic exercise and/or strength training with a cognitive reserve "boosting" intervention on outcomes and recovery following stroke. Aerobic exercise and/or strength training in conjunction with a cognitive reserve "boosting" intervention might demonstrate synergistic or complementary treatment effects above and beyond standalone physical or cognitive interventions (eg, Bo et al 75 and Ploughman et al 76 ). However, the amount, sustainability, and maintenance of a brain and/or cognitive reserve "boosting" intervention, and which cognitive reserve factors would facilitate the greatest protection against impairment or decline remains unknown.…”
Section: The Significance Of Cognitive Reserve For Stroke Impairment mentioning
confidence: 99%
“…Future research should explore the benefits of combining aerobic exercise and/or strength training with a cognitive reserve "boosting" intervention on outcomes and recovery following stroke. Aerobic exercise and/or strength training in conjunction with a cognitive reserve "boosting" intervention might demonstrate synergistic or complementary treatment effects above and beyond standalone physical or cognitive interventions (eg, Bo et al 75 and Ploughman et al 76 ). However, the amount, sustainability, and maintenance of a brain and/or cognitive reserve "boosting" intervention, and which cognitive reserve factors would facilitate the greatest protection against impairment or decline remains unknown.…”
Section: The Significance Of Cognitive Reserve For Stroke Impairment mentioning
confidence: 99%
“…IGF-1 might participate in behaviorally induced plasticity [93,94] whereas BDNF, whose effects and mechanism of action will be discussed in more detail below, is thought to be one potential element linking PA with memory, neurogenesis and synaptogenesis.…”
Section: Improved Neuronal Plasticitymentioning
confidence: 99%
“…Induced by circulating growth hormone (GH), IGF-1 is primarily produced by the liver before being released into the circulatory system. Various reports indicate that IGF-1 is released by other tissues including the skeletal muscle [93,[179][180][181] playing an active role in mediating the recovery of neuronal function through the PA together with BDNF, despite an excessive release of IGF-1 is reported to have opposite effects, inducing an increased level of neuroinflammation and the worst outcome [182]. The attempt to assess if acute exercise effects peripheral IGF-1 levels in humans lead to conflicting results [183,184], although Rojas Vega et al reported a plasmatic increase of IGF-1 (but not of BDNF) levels after a single bout of resistance training [185], Sillanpaa et al [186] report an 8% (p = 0.097) increase after 21 weeks of endurance training in healthy old women and Cappon et al [187] showed that 10-min above-lactate threshold cycle ergometer exercise led to a brief and small increases in circulating IGF-I that were independent of circulating GH, other authors failed to obtain similar results [152,169,170,188].…”
Section: Insulin Growth Factor (Igf)-1mentioning
confidence: 99%
“…Similarly, Brain Derived Neurotrophic Factor (BDNF) has been implicated as mediating improved spatial memory in a trial of aerobic exercise training in older adults, where training increased hippocampal volume, effectively reversing age-related loss by 1 to 2 years 30 . A recent phase II clinical trial in patients with post-stroke cognitive impairment, showed that exercise paired with cognitive training did improve fluid intelligence, but the relationship to BDNF was less clear 31 . It is here that animal models provide a much more fine-grained approach to understanding the intricacies of the cellular and genetic substrates that underpin human cognition 32 .…”
Section: Candidate Therapies For Cognitive Rehabilitationmentioning
confidence: 99%